Do both US and foreign macro surprises matter for the intraday exchange rate? Evidence from Japan - Rasmus Fatum; Michael Hutchison; Thomas Wu (University of California, Santa Cruz Institute for International Economics (SCIIE), 2008)
No previous study has considered the intraday JPY/USD exchange rate responses to a broad set of comparable news surprises from both the U.S. and Japan. We attempt to fill this gap in the literature by investigating the effects of both U.S. and Japanese news surprises, measured as the difference between macroeconomic announcements and preceding survey expectations, on the intraday JPY/USD exchange rate. We show that, overall, Japanese news surprises exert a similar influence on the 5-minute JPY/USD exchange rate returns as U.S. news surprises and, specifically, two of the four most influential macro news emanate from Japan. This finding is robust across three different estimation procedures. In addition, we find asymmetric effects across positive and negative Japanese news surprises when looking at individual Japanese news separately. We also find that the intraday JPY/USD exchange rate responds to a broader set of both U.S. and Japanese news when the Japanese economy is in an upturn, yet it is even more responsive to the consistently most important types of both U.S. and Japanese news when the Japanese economy is in a downturn. Our results show that Japanese macroeconomic news surprises matter for the intraday JPY/USD exchange rate, as do the direction of news surprises and the state of the Japanese business cycle and, therefore, focusing on U.S. news while disregarding foreign news misses half the story.
Keywords: F31; G15; C22; 330; foreign exchange rates; intraday data; macroeconomic news effects; Wechselkurs; Ankündigungseffekt; Konjunktur; Japan; USA